2015
DOI: 10.1039/c5cc04523a
|View full text |Cite
|
Sign up to set email alerts
|

Engineering polypeptide folding through trans double bonds: transformation of miniature β-meanders to hybrid helices

Abstract: Utilization of conjugated double bonds to engineer the novel folded miniature β-meander type structures, single step transformation of miniature β-meanders into ααγ(4)-hybrid peptide 10/12-helices using catalytic hydrogenation, their solution and single crystal conformations are reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…b-Meander is ap rotein super secondary structural motif wherein consecutive b-strands are anti-parallelly arranged, forming am ultiply-linked hairpin structure. [13] Fort he pericyclic 1,3-dipolar cycloaddition reaction between azide and alkyne,they have to be ideally in aparallel or anti-parallel orientation within athreshold distance for the effective head-on orbital overlap of their p-orbitals.I nt he crystal lattice of dipeptide 1,t hough molecules are head-totail aligned along the b-stack, azide and alkyne units of adjacent molecules are not in distances and geometries (d = 4.95 ; f = 121.78 8 and d = 6.5 ; f = 29.68 8)s uitable for their topochemical reaction (Figure 2e). Though the unfavourable geometry and distance (as per the static crystal structure of dipeptide 1)d on ot support any topochemical reaction, the azide can rotate around C À Nb ond and the propargyl group can rotate around N À CH 2 bond to reach ap arallel/antiparallel orientation provided such motions are sterically favourable.T he void analysis revealed that large voids are present in the crystal lattice,e specially around the azide and alkyne groups,suggesting the possibility of rotational motion (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…b-Meander is ap rotein super secondary structural motif wherein consecutive b-strands are anti-parallelly arranged, forming am ultiply-linked hairpin structure. [13] Fort he pericyclic 1,3-dipolar cycloaddition reaction between azide and alkyne,they have to be ideally in aparallel or anti-parallel orientation within athreshold distance for the effective head-on orbital overlap of their p-orbitals.I nt he crystal lattice of dipeptide 1,t hough molecules are head-totail aligned along the b-stack, azide and alkyne units of adjacent molecules are not in distances and geometries (d = 4.95 ; f = 121.78 8 and d = 6.5 ; f = 29.68 8)s uitable for their topochemical reaction (Figure 2e). Though the unfavourable geometry and distance (as per the static crystal structure of dipeptide 1)d on ot support any topochemical reaction, the azide can rotate around C À Nb ond and the propargyl group can rotate around N À CH 2 bond to reach ap arallel/antiparallel orientation provided such motions are sterically favourable.T he void analysis revealed that large voids are present in the crystal lattice,e specially around the azide and alkyne groups,suggesting the possibility of rotational motion (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Similar CD spectra have been reported for a b-meander-type structure in solution state. [13] Thus it could be concluded that polymerization has progressed along the H-bonded stacks of dipeptide 1 molecules to result in pseudoprotein having b-meander structure (Figure 5d).…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, we have shown an unusual planar structure from 1:1 alternating α‐residues and E ‐vinylogous residues (Figure ) . By using mild catalytic hydrogenation, we transformed the unusual planar structure resulting from 1:1 alternating α‐residues and E ‐vinylogous residues and miniature β‐meanders into 12 [12‐atom H‐bond pseudocycle between C=O( i )⋅⋅⋅NH( i +3)] and 10/12 [alternating 10‐atom H‐bond pseudocycle and 12‐atom H‐bond pseudocycle between C=O( i )⋅⋅⋅NH( i +3)] α,γ 4 ‐hybrid peptide helices, respectively . Since E ‐vinylogous amino acids promote β‐sheet structures in hybrid peptides, we hypothesized that the geometrical constraints of Z ‐vinylogous amino acids could be utilized to design helical structures.…”
Section: Figurementioning
confidence: 99%
“… A) The unusual planar structure resulting from 1:1 alternating α‐residues and E ‐vinylogous residues (Boc‐Aib‐ E γPhe‐Aib‐ E γPhe‐OEt) . B) A miniature β‐meander mimetic consisting of an α,α,γ‐hybrid peptide (Boc‐Leu‐Aib‐ E γPhe‐Leu‐Aib‐ E γPhe‐OEt) . Aib=2‐aminoisobutyric acid.…”
Section: Figurementioning
confidence: 99%